2011
DOI: 10.4314/njbas.v18i2.64315
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Associated with Fresh Tilapia Fish (<i>Oreochromis niloticus</i>) Sold At Sokoto Central Market in Sokoto, Nigeria.

Abstract: ABSTRACT:A research was conducted on bacteria micro flora associated with fresh Tilapia fish (Oreochromis niloticus) sold at Sokoto central market, Sokoto. Nigeria. Sections of the skin, gills and intestine of ten randomly selected fishes were aseptically removed by means of a sterile scalpel and pair of sterile scissors. Four (4g) each of the sections were homogenized in 6 ml of sterile distilled water, which served as the original stock culture. A serial dilution up to 10 9 was carried out, and surface plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 4 publications
9
15
0
Order By: Relevance
“…These results came in accordance with those obtained by Atwa, (2007) and Saad El-Deen, (2014). The percentage frequency of occurrence of Listeria monocytogenes 14.7% these findings is in agreement with other previous studies of Shinkafi and Ukwaja (2010), this may due to two sources of fish contamination which includes; the attack of Listeria from intestinal contents to other fish tissues like muscles, especially when the time from fish death till removing the viscera is more than a few hours (Ertas et al, 2005), cross contamination (fish manipulation, using contaminated equipments and inappropriate transport) (Gudbjornsdottir et al, 2004), it's importance come due to it produces a series of toxins hemolytic, lipolytic, hemorrhagic and pyrogenic which are involved in the disease process, the bacterium can also invade the eye and skin cause conjunctivitis and skin lesions (Bahk, and Marth, 1990). Regarding to Streptococcus agalactiae, a gram-positive bacterium which isolated by 15.4%, that can infect a number of fish species, including freshwater and seawater species, the percent was in accordance with earlier reports of (Baeck et al 2006;Garcia et al 2008;Ye et al 2011;Chen et al 2012).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These results came in accordance with those obtained by Atwa, (2007) and Saad El-Deen, (2014). The percentage frequency of occurrence of Listeria monocytogenes 14.7% these findings is in agreement with other previous studies of Shinkafi and Ukwaja (2010), this may due to two sources of fish contamination which includes; the attack of Listeria from intestinal contents to other fish tissues like muscles, especially when the time from fish death till removing the viscera is more than a few hours (Ertas et al, 2005), cross contamination (fish manipulation, using contaminated equipments and inappropriate transport) (Gudbjornsdottir et al, 2004), it's importance come due to it produces a series of toxins hemolytic, lipolytic, hemorrhagic and pyrogenic which are involved in the disease process, the bacterium can also invade the eye and skin cause conjunctivitis and skin lesions (Bahk, and Marth, 1990). Regarding to Streptococcus agalactiae, a gram-positive bacterium which isolated by 15.4%, that can infect a number of fish species, including freshwater and seawater species, the percent was in accordance with earlier reports of (Baeck et al 2006;Garcia et al 2008;Ye et al 2011;Chen et al 2012).…”
Section: Resultssupporting
confidence: 93%
“…This might be due to the effects of different environmental factors like amount of suspended matter in addition to the amount of wastewater discharge by the drains into the canal. Concerning the results and discussion of bacteriological analysis, for fish a range of total viable count of the three sites analyzed revealed 38.75x10 8 cfug -1 from the skin, 20x10 8 cfug -1 from the intestine 44.5 x10 7 cfug -1and from the gills, this come agree with (Shinkafi and Ukwaja, 2010) they confirm that skin is one of the most common segment that contains bacteria. The frequency of occurrence of bacterial isolates is shown in Table (9) and Figure (6): The results from this research indicate that the bacterial load variations in the three segments of the fishes analyzed the skin, intestine and gills.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The highest total aerobic count was observed in tilapia obtained from wet market H. This result similar to Shinkafi and Ukwaja [14] whom reported the high load of bacteria in tilapia sold in the central market of Sokoto Nigeria. The present study found that tilapia was not delivered as live fish but fresh or chilled fish.…”
Section: Discussionsupporting
confidence: 78%
“…The collected swabs were streaked aseptically on Blood agar and MacConkey agar. The plates were incubated at 37 °C for 18-24 h. Preliminary identification of bacteria was based on colony characteristics of the tested bacteria such as colony description, hemolytic activity on blood agar and enzyme activities of the tested isolates [5]. Then the VITEK 2 ID-GN (Gram negative) card and suspension of the bacteria tubes were manually loaded in the VITEK-2 system.…”
Section: Subjects and Samplesmentioning
confidence: 99%